KUALITAS PELAYANAN PUBLIK PADA KANTOR PERTANAHAN KABUPATEN PASAMAN BARAT - Fatmala, Vingki; Rusli. SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Quality of public services to the community are often used as a benchmark in view of the success of an organization or government agency. Government as service providers strive to provide quality service in accordance with the expectations of society. Therefore, the government provides services in accordance with UU 25 of 2009. Then formation of the Land Office is to facilitate implementation the management of the land certificate. However, there are still complaints from the public about the services that exist in the West Pasaman District Land Office. Based on these problems, the researchers interested in studying how the Quality of Public Services At West Pasaman District Land Office.Concept the theory that researchers use theory according to Agus Dwiyanto, there are several dimensions of quality service include: attitudes officers, service procedures, service time, service facilities, and service charges. This research uses descriptive method with qualitative approach. The data obtained through interviews submitted to informant and then analyzed by researchers.From the results this study indicate that the Public Service Quality On Land Office West Pasaman not running optimally. There are still weaknesses regarding quality of service.Keywords: Quality, Public Service, the Land Office